Analisis Kadar Flavonoid, Fenolik, dan Aktivitas Antioksidan Ekstrak Tangkai Buah Cabe Rawit (Capsicum frutescens L.) - Fadhli, Haiyul; Yuswidia Putra, Diova; Trihardiyanto, Agus; Ulfa Frasesa, Roscha (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2025)
Cayenne pepper (Capsicum frutescens L.) is known to have many medicinal properties, especially its fruit. However, cayenne pepper fruit stalks have not been studied in depth and are only considered waste. This study aimed to ascertain the total flavonoid concentration, phenolic content, and antioxidant activity of the extract derived from cayenne pepper fruit. Sample extraction using multistage maceration with the help of sonication. Using 3 different solvents, namely n-hexane, ethyl acetate, and ethanol in a ratio of 1:4 (b/v), and then sonicated (30 minutes, 20-25 °C, 42 kHz). The spectrophotometric technique using a microplate reader was employed to determine the total flavonoid content (TFC). The Folin-Ciocalteu method was used to determine the total phenolic content (TPC). And the DPPH method with a microplate reader was used to determine the antioxidant activity of ethanol extract. Total flavonoid content of 30.333 ± 1.327 mgQE/g extract, total phenolic content of 16.333 ± 0.890 mgGAE/g extract, and IC50 of 544.82 ± 0.01 µg/mL showed that ethanol extract of chili fruit stalk had weak antioxidant activity.